DETERMINATION OF THE TRACE ELEMENTS IN THE ACCESSORY MINERAL MICROCRYSTALS USING X-RAY FLUORESCENCE ANALYSIS IN ORDER TO PETROLOGICAL, GEOCHEMICAL, ENERGETICAL AND METALOGENIC INVESTIGATION OF THE EARTH CRUST EVOLUTION - BUNKEVYCH, O.; ANDREIEV, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The new promising method of trace element concentration determination in accessory minerals XRF-MP/SG (single grain milliprobe X-ray fluorescence analysis) is considered. The method is compared with the modern microbeam methods (EMP, PMP, SHRIMP, SXRF, LAM-ICP-MS). The solution of XRF-MP/SG problem the x-ray fluorescence dependency on microcrystal composition, form and size is proposed. The possibilities of method application in the solution of the important theoretical and practical scientific problems are demonstrated.